SEX RATIO, GONADO-SOMATIC INDEX AND HEPATO-SOMATIC INDEX OF Coptodon zilli and Oreochromis niloticus INHABITING UREJE RESERVOIR, ADO-EKITI - Balogun, Ayodeji T.; Ajibare, Adefemi O.; Ojo, Olusola B. (FUDMA Journal of Sciences, 2025)
The impacts of fishing activity on the natural stocks of fish are hard to evaluate because of the scarcity of studies on their natural status. Thus, this study investigated the sex ratio, gonado-somatic index (GSI), and hepato-somatic index (HSI) as some aspects of the reproductive biology of Coptodon zilli and Oreochromis niloticus of Ureje reservoir, Ado Ekiti Nigeria. 296 samples were collected between October and December from fishermen operating on the reservoir. The sexes were determined by visual inspection while individual gonad and liver were dissected from fish to determine the GSI and HSI respectively. The sex ratio did not significantly deviate from the expected 1:1 even though there were more males in the reservoir. In C. zilli, GSI was 3.06% in females, 2.98% in males, and 3.01% in combined sexes while in O. niloticus, GSI ranged from 2.59% for females and 2.83% for males while the GSI for combined sexes was 2.75% indicating maturity and normal reproductive physiology. HSI was 1.02 (female), 1.11 (male), and 1.08 (combined sexes) for C. zilli while it was 0.44%, 0.78%, and 0.68% for male, female, and combined sexes of O. niloticus respectively. The HSI reflected that the fish and the reservoir cannot be linked with pollution. The study concludes that the GSI and HSI indicated normal reproductive physiology of the fishes. This study has provided basic information on the biology of C. zilli and O. niloticus of the Ureje reservoir. However, there is a need for further ecological study in the study area.
Keywords: Cichlids; Fish biology; Reproduction; Liver; Inland fisheries